Role of stearoyl CoA desaturase on conjugated Linoleic acid concentration in bovine milk : review (2010)
ABSTRACT: Interesting health benefits have been attributed to the intake of conjugated linoleic acid, CLA (C18:2 cis9, trans-11), which is the main isomer of linoleic acid, and is present in bovine milk. Among those benefits are: cancer prevention, diminished risk for the onset of type II diabetes and cardiovascular disease, modulation of the immune response, and reduction of preeclampsia risk in primigravid women. Although an adequate nutrition of cows has permitted to increase the amount of CLA in their milk, there is variation in CLA concentrations among cows consuming the same diet. It has been suggested that this variation is due either to changes in the activity of stearoyl CoA desaturase (SCD), changes in the gene expression, or to alterations in the ruminal process of biohydrogenation. Research conducted in semimembranosus muscle and subcutaneous adipose tissue of cattle suggests there are two isoforms of SCD.